No vision all drive : memoirs of an entrepreneur - Brown, David (Entrepreneur) (Techstars, 2020)
"Every wonder how a startup comes together -- the people, places, skills, failures, hustle, which makes it all stick and become a real business? This is the story of David and David, two entrepreneurs with lots of energy and less of a roadmap than you might think. In 1993, David Cohen and David Brown founded their first company, Pinpoint Technologies, which grew from a basement startup to a successful multinational company with $50 million in annual sales and over 250 employees. Chronicling the story of that company from its beginnings up to 2003, when it was sold to ZOLL, and beyond, No Vision All Drive is the story of that company and the people who worked there. This book is not about business; it is about people. David and David recount our experiences together, from founding Pinpoint to coming back as Managing Partner at Techstars just one year ago, in the updated and re-released version of his book, No Vision All Drive"--